Formulation and development of plasma volume expander using natural and modified starch from Solanum tuberosum - Thombre, Nilima A.; Vishwakarma, Ajit V.; Jadhav, Trupti S.; Kshirsagar, Sanjay J. (International Journal of Pharmaceutical Investigation)
Background: To formulation and development of plasma volume expander (PVE) by using natural and modified starch from Solanum tuberosum. The function of blood circulation is to provide the needs of the body tissues and to maintain an appropriate environment in all tissue fluids of the body for the optimal survival and functions of the cells. Rapid restoration of the blood volume is necessary to decrease reduction in the amount of the blood. The PVEs are isotonic colloidal solutions, act by increasing the osmotic pressure of the intravascular compartment, which leads to the influx of the interstitial fluids through the capillary pore which, in turn, leads to the increase in the volume of the blood. Therefore, there is a need to discover the PVE with less side effects. The main aim of the present study is to use amylopectin as PVEs, fractionated from natural and modified starch obtained from S. tuberosum. Methods: The starch extracted from the normal grains and the tubers of potatoes was selected for the production of starch. Statistical analysis includes in vitro characterization that involves viscosity studies, plasma–product interaction, osmotic pressure detection, molecular weight–viscosity relationship, determination of weight average molecular weight, enzymatic interaction, and in vivo characterization such as toxicity studies and the effect of the products on the blood coagulation. The isolated starch and fractionated amylopectin were analyzed for the physicochemical characteristics. Result and Conclusion: The amylopectin fractionated from isolated starch from grains and tubers of potatoes can be used as PVE, as per the outcome of the study.
Keywords: Amylopectin; fractionated starch; plasma volume expander; Solanum tuberosum